The impact of human capital on the formation of an innovative economy - Kocherbayeva, A.A.; Stybayeva, A.Z. (BUKETOV BUSINESS REVIEW, 2018)
This article examines innovations in the economy and human capital, which form a complex of knowledge necessary to create new or transform old products. The prerequisites for combining innovations and human capital are analyzed, according to which the productivity of the enterprise directly depends on the qualitative composition of the human capital of the enterprise. The concept of «human capital» is expanded and detailed with the help of an innovative component, the author proposes to consider «innovative human capital» as the ability of an employee to improve already existing knowledge and introduce new ideas, solutions and innovations for their transformation. At the same time, an important role in the formation of innovative human capital is played by the thinking of the worker himself, open to the perception of a new, previously unknown knowledge. Given the current realities of economic development, its innovative orientation and considering innovative human capital, it is necessary to identify the level of its development and conduct its evaluation to identify the degree of innovative development of the economy as a whole, we believe that these conditions are the key factor that is necessary in the development of the economy of any country